2011
DOI: 10.1084/jem.20111313
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of TDP-43 in amyotrophic lateral sclerosis triggers nuclear factor κB–mediated pathogenic pathways

Abstract: TDP-43 interacts with and coactivates NF-κB p65 in the spinal cord of amyotrophic lateral sclerosis (ALS) patients, and an NF-κB inhibitor suppresses ALS disease symptoms and neuromuscular junction denervation in an ALS mouse model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
259
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 289 publications
(273 citation statements)
references
References 65 publications
13
259
1
Order By: Relevance
“…Furthermore, Thaiparambil et al (2011), in their study on the effect of WA on breast cancer invasion, showed that treatment of mice with a 4 mg/kg (body weight) dose of WA lead to plasma concentrations of 2 mM, which is comparable to the concentrations used here. Another study on the effect of WA on an ALS mouse model, reports that WA crosses the blood brain barrier (Swarup et al, 2011). Overall, concentration of WA chosen in this manuscript for SILAC analysis is comparable to other published reports of both in vivo and in vitro studies.…”
Section: Resultssupporting
confidence: 75%
“…Furthermore, Thaiparambil et al (2011), in their study on the effect of WA on breast cancer invasion, showed that treatment of mice with a 4 mg/kg (body weight) dose of WA lead to plasma concentrations of 2 mM, which is comparable to the concentrations used here. Another study on the effect of WA on an ALS mouse model, reports that WA crosses the blood brain barrier (Swarup et al, 2011). Overall, concentration of WA chosen in this manuscript for SILAC analysis is comparable to other published reports of both in vivo and in vitro studies.…”
Section: Resultssupporting
confidence: 75%
“…NF‐ĸB is activated in glia in fALS and sALS patients, and astrocytes derived from human postmortem ALS patients showed NF‐ĸB as the highest‐ranked regulator of inflammation in gene array data (Lasiene and Yamanaka, 2011; Swarup et al, 2011). NF‐ĸB can also drive the transcription of TNFα and many other inflammatory molecules (Pękalski et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Mutations in optineurin and more recently, tank binding kinase 1, have been discovered to cause ALS and are known regulators of TNFα signaling and NF‐kB. Interestingly, both TDP‐43 and FUS have been previously been shown to directly bind to NF‐ĸB (Swarup et al, 2011; Uranishi, 2001) and augment its function. The study of FUS and NF‐kB interactions however is limited to just a single study that was carried out prior to discovery of FUS as an ALS gene.…”
Section: Discussionmentioning
confidence: 99%
“…enhance microglia-mediated neuronal cytotoxicity (Swarup et al, 2011 AP-1 is another transcription factor upregulated in microglia following incubation with TDP-43. An AP-1 inhibitor blocked TNF-α and IL-1β protein production more than their mRNA expression.…”
Section: Accepted Manuscriptmentioning
confidence: 99%